Simulation of a multimaterial model for modified auxetic structures - Alexander Engel; Anne Jung (Acta Polytechnica CTU Proceedings, 2023)
Auxetic structures, which is a term used to describe materials with a negative Poisson’s ratio, show beneficial properties like a low density, a high energy absorption capacity and an increased indentation resistance. This enables applications in many fields, such as aerospace and sports industries. Given their potential, many studies have already been conducted. Previously, the geometry of a selected auxetic re-entrant structure was optimized to maximize its mass-specific energy absorption capacity for ideal usage in lightweight applications. Moreover, a homogeneous material was used, whereas the combination of multiple materials could drastically increase the performance of such structures. Hence, in this study the use of two different materials combined into a modified re-entrant structure is investigated via Finite Element simulation. The Poisson’s ratio could thus be improved, which leads to a more pronounced and longer lasting auxetic effect.